Urgensi Pembentukan Peraturan Daerah Kawasan Tanpa Rokok untuk Mewujudkan Lingkungan Bersih dan Sehat di Simalungun - Desiana Sirait; Ronny Andre Chistian Naldo; Muldri P. J Pasaribu (Universitas Medan Area, 2026)
This study analyzes the urgency of establishing a Regional Regulation on Smoke-Free Areas in Simalungun Regency and the legal responsibility arising from its unrealized formation. This research uses normative legal method with statutory and conceptual approaches. Data were obtained from primary, secondary, and tertiary legal materials, supported by relevant field information. The findings show that the formation of a Smoke-Free Area Regulation has a juridical basis in Article 443 paragraph (1) of Government Regulation Number 28 of 2024 and is related to the fulfillment of public rights to health and a clean and healthy environment. Its urgency lies in the need to provide an operational legal basis for regulating, supervising, guiding, and enforcing smoke-free areas. However, legal responsibility remains limited because there is no explicit sanction for local government or regional parliament that has not followed up the mandate. This condition indicates the need for clearer regulatory enforcement mechanisms locally.